CFD SIMULATION OF GAS SEPARATION IN DIVERGING T-JUNCTION - ZAIN EL BYTTEE, SABRINA (IRC, 2021)
T-junction is used as an efficiency separator to tap gas resource in offshore platform, using the physical fact that liquid is heavier than gas.